Leaf-Litter Mixtures Affect Breakdown and Macroinvertebrate Colonization Rates in a Stream Ecosystem - Abelho, Manuela (International Review of Hydrobiology, 2009)
Previous work in terrestrial and aquatic ecosystems has suggested that the relationship between breakdown rates of leaf litter and plant species richness may change unpredictability due to non-additive effects mediated by the presence of key-species. By using single- and mixed-species leaf bags (7 possible combinations of three litter species differing in toughness; common alder [Alnus glutinosa ], sweet chestnut [Castanea sativa ], and Spanish oak [Quercus ilex ilex ]), I tested whether leaf species diversity, measured as richness and composition, affects breakdown dynamics and macroinvertebrate colonization (abundance, richness and composition) during 90 days incubation in a stream. Decomposition rates were additive, i.e., observed decomposition rates were not different from expected ones. However, decomposition rates of individual leaf species were affected by the mixture, i.e., there were species-specific responses to mixing litter. The invertebrate communities colonizing the mixtures were not richer and more diverse in mixtures than in single-species leaf bags. On the opposite, mixing leaf species had a negative, non-additive effect on rates of shredder and taxa colonization and on macroinvertebrate diversity. (© 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
The following values have no corresponding Zotero field: publisher: WILEY-VCH Verlag
Keywords: Biodiversity; decomposition; FOREST; richness; shredders

Leaf-Litter Mixtures Affect Breakdown and Macroinvertebrate Colonization Rates in a Stream Ecosystem (International Review of Hydrobiology, 2009)
Previous work in terrestrial and aquatic ecosystems has suggested that the relationship between breakdown rates of leaf litter and plant species richness may change unpredictability due to non-additive effects mediated by the presence of key-species. By using single- and mixed-species leaf bags (7 possible combinations of three litter species differing in toughness; common alder [Alnus glutinosa ], sweet chestnut [Castanea sativa ], and Spanish oak [Quercus ilex ilex ]), I tested whether leaf species diversity, measured as richness and composition, affects breakdown dynamics and macroinvertebrate colonization (abundance, richness and composition) during 90 days incubation in a stream. Decomposition rates were additive, i.e., observed decomposition rates were not different from expected ones. However, decomposition rates of individual leaf species were affected by the mixture, i.e., there were species-specific responses to mixing litter. The invertebrate communities colonizing the mixtures were not richer and more diverse in mixtures than in single-species leaf bags. On the opposite, mixing leaf species had a negative, non-additive effect on rates of shredder and taxa colonization and on macroinvertebrate diversity. (© 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)